A Cross-sectional Study to Assess the Eating Disorder Among Female Medical Students in A Rural Medical College of Karnataka State - Shashank KJ; Gowda, Praveen; Chethan TK (National Journal of Community Medicine, 2016)
Background: Eating Disorder is real complex and divesting condi- tion that can have serious consequences for health, productivity and relationships. They have serious potentially life threatening condition that affects a person’s emotional and physical health. Unfortunately, the diagnosis of eating disorders can be elusive, and more than one half of all cases go undetected. Objective of the study was to assess the prevalence of abnormal eating attitudes among female medical students in a Medical College. Materials and Methods: A Cross Sectional study was conducted from December 2015 to March 2016 among the female medical students in Adichunchanagiri Institute of Medical Sciences. EAT 26 and SCOFF questionnaire was used to obtain the data. Results : A total of 134 female medical students participated in the study.EAT 26 Questionnaire revealed that nearly 39 (29.2%) of the students had eating attitude and behaviour problem. 23 (17.2%) students scored SCOFF score of greater than 2. Conclusion: The prevalence of eating disorders among the Female medical students can be easily detected using the both Question- naire. EAT 26 Questionnaire revealed more percentage of students with eating disorder than SCOFF. The SCOFF and EAT 26 ques- tionnaire is easy, effective, simple and memorable to apply and also to evaluate by the healthcare professionals.